THE INFLUENCE OF DEMONSTRATION METHOD ON STUDENT LEARNING OUTCOMES IN CHRISTIAN RELIGIOUS EDUCATION SUBJECT FOR 10TH GRADE STUDENTS AT KARYA AGUNG VOCATIONAL HIGH SCHOOL - Saragih, Novita Romauli; Karo, Selamat Karo-; Wiharjokusumo, Padriadi; Manalu, Managor; Panjaitan, Jelita; Naiborhu, Murni (JURNAL DARMA AGUNG, 2023)
This study aims to determine the effect of the demonstration method on student learning outcomes in the subject of Christian Religious Education in grade X of Karya Agung Vocational High School in Bagan Batu Sinembah, Rokan Hilir, Riau, in the academic year 2022, and to determine the effect of conventional teaching methods on student learning outcomes in the subject of Christian Religious Education in grade X of Karya Agung Vocational High School in Bagan Batu Sinembah, Rokan Hilir, Riau, in the academic year 2022. This type of research is an experiment. The population in this study was all grade X students of Karya Agung Vocational High School in Bagan Batu Sinembah, Rokan Hilir, Riau, in the academic year 2022, consisting of 60 students in 2 parallel classes. The sample in this study consisted of two classes, namely class X-1 as the experimental class taught with the demonstration method and class X-2 as the control class taught with conventional teaching methods. From the results of the study, it was concluded that there is a significant influence of the demonstration method on student learning outcomes in grade X of Karya Agung Vocational High School in Bagan Batu Sinembah, Rokan Hilir, Riau, in the academic year 2022. This is based on the hypothesis test, where the obtained result is tcount of 3.90, while the ttable is 1.67, which means that tcount > ttable (3.90 > 1.67). If tcount is greater than ttable, then the demonstration method has a significant influence on student learning outcomes.